Aplicación de Estrategias Metodológicas para mejorar el proceso de aprendizaje en Lengua y Literatura en los Niños de Tercer Grado - Changoluisa Jaya, Lilia Germania (2022)
The work carried out is focused on didactic strategies to improve the learning process of Language and Literature in third grade children, where its general objective is to apply methodological strategies that allow improving the learning process of Language and Literature, in the students of third grade of basic education, where the main beneficiaries will be the students of the third years of basic education of the School of Basic Education "Juan Manuel Lasso", the methodological approach of this research project is quantitative since it is a contribution that will allow the application of methodological strategies based on the didactic or recreational activities previously planned in the proposal, the same ones that will allow improving the teaching process of Language and Literature, taking into account that the components of Language and Literature are writing and reading and are the basis for the development of literacy skills in the students. Therefore, the proposal for the Application of Methodological Strategies was proposed to improve the learning process in Language and Literature in third grade children of the "Juan Manuel Lasso" School of the Tanicuchi Parish in the 2021 - 2022 school year, having As favorable results, the improvement in writing and reading by 90% during the learning process in third grade students, achieving in itself the strengthening of their educational process by improving their academic level.